Burden of venous leg ulcers in the United States. (May 2014) - Rice, J. Bradford; Desai, Urvi; Cummings, Alice Kate G.; Birnbaum, Howard G.; Skornicki, Michelle; Parsons, Nathan
Abstract Objective: To estimate the annual incremental per-patient and overall payer burden (2012USD) of venous leg ulcers (VLU) in the US. Methods: Beneficiaries with and without VLU were identified using two de-identified insurance claims databases: aged 65+ from a 5% random sample of Medicare beneficiaries (2007–2010: n ∼ 2.3 million); and aged 18–64 from a privately-insured population (2007–2011: n ∼ 8.4 million). The index date was selected as the date of a VLU claim with no other VLU diagnoses in the preceding 12 months for the VLU cohort and as the date of a random medical claim for the non-VLU patients. These groups were matched using propensity scores to account for differences in demographics, comorbidities, resource utilization, and costs in the 12 month pre-index period. Medical resource use and costs incurred during the 12 month follow-up period were calculated for both payers. Drug costs and indirect work-loss due to disability and medically-related absenteeism were estimated for the privately-insured sample only. Annual VLU incidence rates were also estimated for both payers. Results: Data for 58, 672 matched VLU/non-VLU pairs of Medicare and 22, 476 matched pairs of privately-insured patients were analyzed. Relative to matched non-VLU patients, VLU patients used more medical resources and incurred annual incremental medical costs of $6391 in Medicare ($18, 986 vs $12, 595), and $7030 ($13, 653 vs $6623) in private insurance ($7086 including drug costs). Compared with non-VLU patients, privately-insured VLU patients had more days missed from work (14.0 vs 10.0), resulting in 29% higher work-loss costs (comparisons significant at p < 0.0001). The average annual incidence rate of VLU was 2.2% in Medicare and 0.5% in private insurance. Limitations: Findings did not account for out-of-pocket payments or other indirect costs (e.g., lost productivity), and relied on accuracy of diagnosis and procedure codes contained in claims data. Conclusion: These findings suggest an annual US payer burden of $14.9 billion.